Mainstreaming Urban Interventionist Practices: the Case of the BMW Guggenheim Lab in Berlin - Monika Grubbauer (Footprint)
The paper examines how practices of urban intervention have entered the mainstream by discussing the case of the BMW Guggenheim Lab. Financed by the German BMW group and realised by the Solomon Guggenheim Foundation, the project addresses issues of contemporary urban life in the form of a ‘mobile laboratory’ with an explicit emphasis on participatory forms of urban intervention. The Lab’s temporary residence in Berlin in 2012 encountered fierce protests from residents and activist groups.